Treatment of high-strength ammonium wastewater by polyvinyl alcohol–sodium alginate immobilization of activated sludge. (December 2017) - Xu, Xiaoyi; Jin, Zhaoxia; Wang, Bin; Lv, Chenpei; Hu, Bibo; Shi, Dezhi
Graphical abstract: Highlights: Immobilization technology was suitable for the high-strength ammonium wastewater. The maximum ammonium removal load was 60.84–240.15 mgN/(L-particles h). Immobilized beads had a dense network structure that was suitable for microbial growth. Heterotrophic nitrifying and aerobic denitrifying bacteria may provide unconventional denitrifying pathways. Abstract: We employed microorganism embedding immobilization technology to treat high-strength ammonium(NH4 + -N) wastewater. Experiments were conducted in batch reactors with different initial ammonium concentrations (50–400 mg/L), 10% particle dosage rates, 7.5–8.5 pH, and 495-min operation cycle. Stable treatment efficiency was reached in the 28th, 40th, 55th, 58th, and 58th cycles with average ammonium removal rates of 100, 100, 80.9, 64.6, and 48.0%, respectively. The ammonium removal reaction followed zero-order reaction kinetics. Brunauer-Emmett-Teller (BET) and Scanning Electron Microscopy (SEM) demonstrated that the specific surface area and pore size of beads in stable phase were larger than corresponding values for the unused embedding beads, and microorganisms were found in the interior and external surface of beads. High-throughput sequencing illustrated that the microbial community composition significantly differed between the interior and external surface of embedding beads. And the existence of heterotrophic nitrifying and aerobic denitrifying bacteria may provide additional pathways for biological nitrogen removal in the reactors.